Effects of risk factors on the interruption of studies in university students during COVID-19 - Miranda Rodríguez, Víctor José (2021)
An issue faced by university students in the current situation resulting from the pandemic is how to continue as students, and not follow the fate of their classmates who have abandoned their studies. The goal of this article is to address the effects of risk factors on the interruption of studies in university students during the COVID-19 pandemic. The subjects of the study were students in their fourth semester at a private university, and the conclusive results indicate that student dropout rates are related to four factors: family, motivational, institutional and financial. The institutional factor was influential, given that support was not adjusted in response to financial issues; however, the financial risk factor was most relevant in the decision of students to abandon their studies, either temporarily or partially, and also, as occurred in several cases, permanently.